Small and Medium‐Sized Enterprises and Sustainability: Managers' Values and Engagement with Environmental and Climate Change Issues. (24th May 2012) - Williams, Sarah; Schaefer, Anja
ABSTRACT This article reports on an in‐depth, qualitative study into the pro‐environmental engagement of small businesses in the east of England, with respect to climate change in particular. Managers of environmentally pro‐active small businesses were asked about the pro‐environmental measures they had implemented in their firms, their motivations for doing so, and their understanding of climate change. The managers in this study had a relatively good understanding of environmental issues in general and climate change in particular, and had implemented a range of pro‐environmental measures in their firms. Their understanding of climate change was a holistic one, which sat within their overall understanding of environmental and social issues. While economic arguments and external pressure played a role in their pro‐environmental engagement, perhaps the most notable motivation for managers in this study to engage with environmental and climate change issues was personal values and beliefs. Environmentally engaged managers exhibited an internal locus of control. Some of these findings contrast with the views of key informants in local government and business advice organisations, who tend to emphasise the business case and cost arguments when trying to encourage small businesses towards greater environmental engagement. These findings suggest that public policy and business advice in this area should perhaps focus more strongly on personal values and a sense of being able to contribute to environmental protection in their engagement with small businesses. Copyright © 2012 John Wiley & Sons, Ltd and ERP Environment.